VD_FINDINFO HC / 2022 / 975 vom 7. November 2022 - VD Tribunal cantonal (2022)
DÉPENS, DROIT D'ÊTRE ENTENDU, AVOCAT D'OFFICE, INDEMNITÉEN GÉNÉRAL | 113 al. 1 CPC (CH), 122 al. 1 let. a CPC (CH), 198 CPC (CH)